International Society of Sports Nutrition Position Stand: Probiotics - Jäger, R.; Mohr, A. E.; Carpenter, K. C.; Kerksick, C. M.; Purpura, M.; Moussa, A.; Townsend, J. R.; Lamprecht, M.; West, N. P.; Black, K.; Gleeson, M.; Pyne, D. B.; et al. (Journal of the International Society of Sports Nutrition, 2019)
Position statement: The International Society of Sports Nutrition (ISSN) provides an objective and critical review of the mechanisms and use of probiotic supplementation to optimize the health, performance, and recovery of athletes. Based on the current available literature, the conclusions of the ISSN are as follows: